Health and Care in Ageing Societies : A New International Approach - Lloyd, Liz (Book collections on Project MUSE., 2012)
Offering a critical analysis of the limitations of contemporary policies, this book calls for a fuller understanding of the relationship between health and care throughout the lifecourse.